Tomato severe rugose virus: exploring the potential of soybean as source of inoculum and no evidence of horizontal or vertical transmission by Bemisia tabaci MEAM1 - Favara, Gabriel Madoglio (2022)
Tomato (Solanum lycopersicum) is one of the main vegetables worldwide. Virus infections are among the causes that can reduce tomato production. In Brazil, the tomato severe rugose virus (ToSRV) is one of the most critical viruses in tomato crops. ToSRV, a member of the genus Begomovirus, is transmitted by the whitefly Bemisia tabaci in a persistent circulative manner. ToSRV has a wide host range, including cultivated and weed plants. Recently, it was found that soybean (Glycine max) plants can play an essential role in the epidemiology of ToSRV by acting as an amplifier host of the virus and providing sufficient inocula for epidemics of this begomovirus in tomato crops. Because of the importance of this attribute, the potential of soybean plants as a source of ToSRV inoculum needs to be further explored. Some begomoviruses can be transmitted vertically to the progeny of viruliferous females of B. tabaci. Horizontal transmission of begomoviruses during sexual reproduction between B. tabaci males and females was also described. Vertical and horizontal transmission can be highly important for the epidemiology of the disease caused by ToSRV, since the viral inoculum can remain in the vector without the need for virus host plants in the field. This study explored the potential of soybean plants as sources of ToSRV inoculum and determined if this begomovirus is transmitted vertically or horizontally by B. tabaci MEAM1. The results showed that soybean plants could be good sources of ToSRV inoculum. Also, ToSRV was not vertically transmitted to the progeny of viruliferous females of B. tabaci MEAM1 and was not horizontally transmitted during mating between males and females of this vector. These results provided important information related to the epidemiology of ToSRV, and should be taken into account in the management of this begomovirus in tomato crops.